The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3389/fmicb.2018.01156
|View full text |Cite
|
Sign up to set email alerts
|

Current Trends and Potential Applications of Microbial Interactions for Human Welfare

Abstract: For a long time, it was considered that interactions between microbes are only inhibitory in nature. However, latest developments in research have demonstrated that within our environment, several classes of microbes exist which produce different products upon interaction and thus embrace a wider scope of useful and potentially valuable aspects beyond simple antibiosis. Therefore, the current review explores different types of microbial interactions and describes the role of various physical, chemical, biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(65 citation statements)
references
References 138 publications
0
62
0
Order By: Relevance
“…In contrast, the co-culture of the weak candidates (P. nobilis and Lentithecium sp.) displayed mutual interaction [37] as fungal mycelia grew freely into each other.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the co-culture of the weak candidates (P. nobilis and Lentithecium sp.) displayed mutual interaction [37] as fungal mycelia grew freely into each other.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, these anti-QS reagents (allicin, triazolyldihydrofuranone and baicalin hydrate) are effective against multidrug-resistant P. aeruginosa [33,34,35]. Studies in the past decade revealed that these anti-QS reagents also inhibited many human infections caused by biofilm-producing bacteria [52,53]. This fact is important for fighting human pathogenic bacteria, as biofilms are found to be involved in over 80% of microbial infections in humans [54].…”
Section: Discussionmentioning
confidence: 99%
“…Microorganisms are ubiquitous inhabitants of natural and unnatural ecosystems, and growth of them in a sessile lifestyle inevitably form communities composed of homo-/heterogeneous species with complex ecological interacting networks (Griffin et al, 2004; Adnani et al, 2017; Tshikantwa et al, 2018). Microbial species in symbiotic communities evolve kinds of chemical or physical interaction patterns such as metabolite-mediated cooperation/conflict and space competition, and these interactions can be beneficial, neutral or harmful to the fitness of individuals in the community.…”
Section: Introductionmentioning
confidence: 99%